Dar corpo à didática: diálogos internacionais - Giaconi, Catia; Rodrigues, Maria Beatriz; Capellini, Simone Aparecida [UNESP]; Rossi, Pier Giuseppe (CEFAC Saúde e Educação, 2014)
The article uses theoretical approaches as simplexity, neuroscience and enactivism to discuss everyday classroom activities. It tries to transpose the classical bipolar division between mind and body, through these approaches in cognitive science. Two experiments on the body’s role in teaching are presented to demonstrate the relevance of the awareness of the body, to improve performance in the classroom. The first experiment uses neurofeedback to measure the body temperature, as a means to understand the role of the body in self-regulation and control of the attention. The second uses a bracelet multi-sensor, which provides data on the energy spent by the teacher in daily activities in the classroom. Italian and Brazilian researchers cooperate in this experimental path of inclusive teaching, to be used in classes with children and adolescents with Attention Deficit Hyperactivity Disorder.

O artigo utiliza abordagens teóricas como simplexidade (simplexity) , neurociências e enactivismo para discutir cenários cotidianos de sala de aula. Busca transpor a clássica divisão bipolar entre mente e corpo, por meio destas abordagens das ciências cognitivas. Dois experimentos sobre o papel do corpo na didática são apresentados para demonstrar a relevância da conscientização do corpo, para melhorar o desempenho em sala de aula. O primeiro experimento utiliza o neurofeedback para medir a temperatura corporal, como meio para entender o papel do corpo na auto-regulação e gestão da atenção. O segundo utiliza um bracelete multi-sensor, que fornece dados sobre a energia gasta pelo professor nas atividades cotidianas em sala de aula. Pesquisadores italianos e brasileiros cooperam para que esta trajetória experimental de didática inclusiva, seja utilizada em classes com crianças e adolescentes com Déficit de Atenção e Hiperatividade.
Shaping the teaching: international dialogues
Keywords: Didática; Simplexidade; Enactivismo; Neurofeedback; Didactics; Simplexity; Enactivism; Neurofeedback